Factors and mechanisms of coronary atherosclerosis and its complications - Yu. I. Ragino (Атеросклероз, 2012)
Reference to the report at the meeting of the Presidium of the Siberian Branch of the Russian Academy of Medical Sciences on January 25, 2012